A Comprehensive Bibliometric Analysis of School-Based Physical Activity Research - Dofredo, Kyla H.; Pinlac, Jelene T.; Pineda, Kylah R.; Gatus, Lovely L.; Briñas, Norlito Nickson N.; Miranda, John Paul P.; Tolentino, Julius Ceazar G. (Future Science / FSH-PH Publications, 2023)
Physical activity has captured considerable interest from international academic scholars due to its fundamental role in maintaining optimal health. Thus, this study sought to examine the scholarly articles on school-based physical activity, employing a comprehensive bibliometric analysis extracted from the Scopus database spanning 2013 to 2023. A filtering protocol was utilized to guide the selection of articles, and analyses were facilitated solely by Python programming. This research yielded extensive insights encompassing document type, publication rates, citation rates, prevalent keywords, and geographic distribution. The results revealed the prominence of